Malarigen malaria pf/pv antigen rapid test: a simple and effective tool for diagnosis of malaria in the far-flung hilly areas of Bangladesh - Selimuzzaman, SM; Islam, SJ; Nahar, Z; Das, R; Rahman, MA; Rahman, MA (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jan;19(1):94-99. The abstract of this article is available on the PubMed website